Pengaruh Dosis Pemberian Pupuk NPK Mutiara terhadap Pertumbuhan dan Produksi Kacang Panjang (Vigna Sinensis L.) - Elva Pobela; Agustinus Mokoginta; Henratno Pasumbuna; Meysi Mamonto (JTPG (Jurnal Teknologi Pertanian Gorontalo), 2022)
Vegetables are stapled food companion ingredients that must be present in the composition of food consumed by humans. This is because in vegetables there are substances that are needed by the body. Not only to maintain body immunity, but vegetables are also sometimes often used to prevent and treat disease. Increasing demand for vegetable demands increased production as well. However, there are several obstacles that can reduce productivity, including planting media (soil), pests and diseases, as well as the dosage of fertilizer application. One type of vegetable that is widely consumed by the public is long beans. One of the aims of this study was to determine the effect of NPK Mutiara fertilizer on the growth and production of long beans. This research was carried out in the form of an experiment in the field using the Randomized Block Design Method (RBD) with 6 treatments repeated 4 times so that there were 24 study plots. Long beans were planted with the treatment of Pearl NPK fertilizer which consisted of 6 treatments, namely: PK 0 (control), PK 1 = 10 gr, PK 2 = 15 gr, PK 3 = 20 gr, PK 4 = 25 gr, PK 5 = 30 gr per plot. Variables observed included vine length, number of pods, and pod weight. Data were analyzed using analysis of variance and if it had a significant effect, then it was continued with the 5% Least Significant Difference (LSD) test. Based on the results of the study it was known that at the age of 10 HST, 20 HST, and 30 HST the application of Mutiara NPK fertilizer had no significant effect on the height of long bean plants (Vigna sinensis L.).